(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2026)
This study aims to analyze the potential for urban connectivity among six public parks located in the city center of Misrata by employing Space Syntax theory tools to examine the relationship between spatial configuration, movement networks, and the public realm. The methodology is based on two main analyses: Axial Analysis and Visibility Graph Analysis (VGA), with the objective of measuring visual integration and connectivity, as well as assessing the capacity of urban axes to enhance both visual and spatial accessibility to these parks. The results indicate that Al-Baladiya Street demonstrates high values of integration and connectivity, qualifying it as a strong urban model that reinforces local identity. This model can be replicated within the urban fabric to form an Urban Loop originating from this street, connecting public parks through shaded green corridors. Such corridors improve mobility, encourage social and cultural interaction, and contribute to revitalizing the public realm in an area characterized by high population density and cultural diversity. These findings provide both a practical and scientific framework that can be applied to other cities with similar urban and social characteristics.